Application of ultrasonic guided exploration of blood vessels without a needle guide in peripherally inserted central catheter placement (超声纵向探查血管脱离导针器穿刺技术在PICC置管中的应用) - LU Zeling (卢泽玲); LIN Han (林翰); WU Qiuxia (巫秋霞) (中西医结合护理, 2022)
Objective To investigate the failure of ultrasound guided peripherally inserted central catheter (PICC) puncture when the vascular depth does not match the type of needle guide. To observe the effect of the novel puncture technology, exploration of vascular puncture without needle guide. Methods With mismatching needle guide kit and vessel depth, 96 cases of ultrasound guided PICC puncture catheter model were included in the study. Based on the random number table method, these cases were divided into two groups: the control group (n=48) and experimental group (n=48). In the control group, the conventional modified Sedinger PICC puncture catheter was used to perform puncture; the novel technique of ultrasonic guided exploration of blood vessels without a needle guide was implemented in the experimental group. The success rate of puncture, mechanical phlebitis, blood loss, puncture cost and operation time were compared between the two groups. Results In the experimental group, the one-time success rate of guide wire implantation was 95. 83%(46/48) and that of the control group was 79. 17%(38/48), which showed a significant difference between the two groups (P＜0. 05). Comparing with the control group, the incidence of mechanical phlebitis, blood loss and puncture time were reduced in the experimental group (P＜0. 05). Conclusion It is convenient that ultrasonic guided exploration of blood vessels without a needle guide. This new technique avoids the bad influence cause by mismatching of needle guide kit, which make it worthwhile in clinical application. (目的 探讨在超声引导经外周静脉置入中心静脉导管 (PICC)穿刺中遇到血管深度与导针器型号不匹配的情况下, 不理想的穿刺角度造成的穿刺失败, 采用脱离导针器纵向探查血管穿刺技术的效果观察。方法 对96例超声引导下PICC穿刺导针器型号与血管深度不匹配的置管患者, 按照随机数字表法分为两组, 对照组48例患者, 采用常规改良赛丁格PICC穿刺置管; 研究组48例患者, 采用无导针器, 超声引导纵向探查血管穿刺置管的方法。比较两组患者一次穿刺成功率、机械性静脉炎(MP)、穿刺时出血量, 穿刺费用及操作时间的差异。结果 研究组一次导丝置入成功率为95. 83%(46/48), 对照组为79. 17%(38/48), 两组比较差异有统计学意义(P<0. 05), 研究组MP发生率、穿刺时出血量及穿刺时间均低于对照组(P<0. 05)。结论 超声引导无导针器纵向探查血管穿刺置管操作直观方便, 不受导针器型号影响, 值得临床推广应用。)